Analisis Putusan Hakim Pengadilan Tindak Pidana Korupsi Denpasar (Putusan No : 42/Pid.Sus-TPK/2015/PN Dps) - I Made Suartana; I Made Minggu Widyantara; I Nyoman Gede Sugiartha (Fakultas Hukum, Universitas Warmadewa, 2020)
The aim and purpose of this research is to analyze â€œthe abuse of authority in official travel orders that have implications for corruption.â€ The legal issues arising out of this research comprises: What is the Legal Basis of Denpasar Corruption Court Judges in taking into consideration and imposing criminal sanctions under Decision No. 42/Pid.Sus-TPK/2015/PN Dps, and What is the Juridical Analysis toward the Decision No. 42/Pid.Sus-TPK/2015/PN Dps issued by Denpasar Corruption Court Judges. This research is a normative legal research adopting a number of approaches i.e. Statute Approach, Conceptual Approach, and Case Approach. Based on this researchâ€™s output may conclude that: 1) Crime/Corruption Offense is a crime specifically governed by Law No. 20 of 2001 of which law was enacted as an amendment to previous Law No. 31 of 1999 that also govern Eradication of Crime or Corruption; 2) By virtue of Decision No. 42/Pid.Sus-TPK/2015/Pengadilan Negeri Denpasar, Defendant was proven to have infringed Article 3 of Law No. 31 of 1999 amended by Law No. 20 of 2001 on Crime/Corruption Eradication that under the decision of which all acts committed by the Defendant have been proven to infringed all elements of crime charged in the subsidiary indictment as follows: 1) Element of â€œEvery personâ€; 2) Element of â€œThe aim of benefiting themselves or other people or a corporationâ€; 3) The Element of â€œAbusing the authority, opportunity or facility provided to him/her due to his/her position or office; and 4) Element of â€œProbable detrimental to the State's finance or economys.â€